2017
DOI: 10.1111/asj.12767
|View full text |Cite
|
Sign up to set email alerts
|

Hampered cumulus expansion of porcine cumulus‐oocyte complexes by excessive presence of alpha2‐macroglobulin is likely mediated via inhibition of zinc‐dependent metalloproteases

Abstract: In vitro maturation (IVM) in serum causes hampered expansion of porcine cumulus-oocyte complexes (COCs) due to excessive alpha -macroglobulin (A2M). This study investigated two hypotheses that could explain the effect of A2M: (i) binding of epidermal growth factor (EGF) to A2M, followed by its decreased availability; and (ii) inhibition of zinc-dependent metalloproteases. Cumulus expansion was evaluated based on the diameter of the COCs, the proportion of COCs participating in a floating cloud and the proporti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…Numerous proteins that contribute to blood coagulation and fibrin degradation through plasminogen (PLG) or proteolysis by thrombin activation [61] were detected. For example, alpha-2-macroglobulin (A2M), a protease inhibitor that binds small or large proteinases such as the plasmin that regulates proteolytic activity [63], influences cumulus cells expansion by inhibiting zinc-dependent metalloproteases [64]. In this way, the excess of A2M lead a reduction in porcine cumulus expansion [64, 65].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous proteins that contribute to blood coagulation and fibrin degradation through plasminogen (PLG) or proteolysis by thrombin activation [61] were detected. For example, alpha-2-macroglobulin (A2M), a protease inhibitor that binds small or large proteinases such as the plasmin that regulates proteolytic activity [63], influences cumulus cells expansion by inhibiting zinc-dependent metalloproteases [64]. In this way, the excess of A2M lead a reduction in porcine cumulus expansion [64, 65].…”
Section: Discussionmentioning
confidence: 99%
“…For example, alpha-2-macroglobulin (A2M), a protease inhibitor that binds small or large proteinases such as the plasmin that regulates proteolytic activity [63], influences cumulus cells expansion by inhibiting zinc-dependent metalloproteases [64]. In this way, the excess of A2M lead a reduction in porcine cumulus expansion [64, 65]. Clusterin (CLU), another protease inhibitor, is an important regulator of the complement [66], preventing apoptosis of follicular cells [67].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, only the LNA protein dataset revealed significant enrichment, and the proteins having the highest number of interactions play important roles on cytoplasmic maturation. Amongst these proteins, plasminogen [47], AMBP [57], and alpha-2-macroglobulin [58] positively influence cumulus expansion, while alpha-2-HS-glycoprotein regulates the binding of spermatozoa on zona pellucida [59], which could influence the incidence of polyspermy in pigs [14]. In addition, the histidine-rich glycoprotein (HRG) protein may act on blood coagulation [60] inhibiting the action of vascular endothelial growth factor [61].…”
Section: Discussionmentioning
confidence: 99%